Morphometric Characteristics of the Spermatozoa of Blue Fox (Alopex lagopus) and Silver Fox (Vulpes vulpes) - Katarzyna Andraszek; Dorota Banaszewska; Olga Szeleszczuk; Marta Kuchta-Gładysz; Anna Grzesiakowska (Animals, 2020)
The results presented in this study are the first such extensive characterization of the sperm morphometry of the blue fox (Alopex lagopus) and silver fox (Vulpes vulpes), as representatives of the family Canidae. Canine spermatozoa, especially the sperm of farmed foxes, are not often described in studies on reproduction. The aim of the study was a detailed comparison of the morphometric dimensions and shape of the sperm of two fox species: silver fox and blue fox. Semen collected from 10 silver foxes and 10 blue foxes was used for the study. The specimens were stained with silver nitrate. Measurements were performed of the length, width, perimeter, and area of the head; the area of the acrosome and its coverage; the length of the midpiece and its coverage; the length of the tail; and the length of the end piece of the tail. In addition, four head shape indices were calculated: ellipticity, elongation, roughness and regularity. The following values for the morphometric parameters and shape indices were obtained for blue fox and silver fox, respectively: head length—6.72 µm and 6.33 µm; head width—4.54.µm and 4.21 µm; head perimeter—18.11 µm and 17.37 µm; head area—21.94 µm2 and 21.11 µm2; acrosome area—11.50 µm2 and 10.92 µm2; midpiece length—12.85 µm and 12.79 µm; tail end piece length—3.44 µm and 3.28 µm; tail length—65.23 µm and 65.09 µm; acrosome coverage—52.43% and 52.83%; midpiece coverage—19.71% and 19.65%; sperm length—71.95 µm and 71.42 µm; ellipticity—1.49 and 1.52; elongation—0.19 and 0.20; roughness—0.84 and 1.88; regularity—1.09 and 0.99. The significance of differences between species was verified by Tukey’s test at p ≤ 0.05. Statistically significant differences between species were found for the following parameters: head length, width, perimeter and area; acrosome area; tail, end piece, and total sperm length; roughness and regularity. The differences in the size and shape of sperm can be used to establish reference patterns for fox sperm enabling more accurate species identification.